IMPLIKASI PENERAPAN MOTIVASI DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI PADA DINAS SOSIAL PROVINSI BALI - Ida Bagus Ngurah Wimpascima; Ni Nyoman Nurani; Reineldis Angela Thay (STIMI Handayani Denpasar, 2022)
This study aims to determine the implications of the application of motivation and communication on employee performance at the social service office of the province of Bali. Respondents used in this study were 68 employees at the Social Service of the Province of Bali. The data that has been collected is tested for validity and reliability first, followed by descriptive statistics and classical assumption tests. After the classical assumption test is fulfilled, the data is processed by multiple linear regression in order to be able to answer the predetermined problem formulation. The results showed that the variables of Communication (X1) and Motivation (X2) partially had a positive and significant effect on the performance of employees (Y) at the Social Service of the Province of Bali.